Many-electron Electrochemical Processes Reactions in Molten Salts, Room-Temperature Ionic Liquids and Ionic Solutions - Andriiko, Aleksandr A. (Monographs in Electrochemistry, 2013)
Here, the authors provide a unified concept for understanding multi-electron processes in electrochemical systems such as molten salts, ionic liquids, or ionic solutions. A major advantage of this concept is its independence of assumptions like one-step many-electron transfers or discrete discharge of complex species. Therefore this monograph is a unique resource for basic electrochemical research but also for many important applications such as electrodeposition, electrorefining, or electrowinning of polyvalent metals from molten salts and other ionic media.